(untitled) (Third Sector Social Economic Review, 2015)
Today, it is observed that three forms of systems of government are implemented in democratic countries. States’ political, historical and economic experiences brought their decision to choose a particular type of systems of government. In this regard, it can be said that every government system has its own historical background. Despite the existence of ruptures in particular periods, Turkey has been governed by parliamentary system since 1876. Nevertheless, contemporarily transition from parliamentary system to presidential system constitutes political agenda in Turkey. Problems in implementation of parliamentary system are the basis of discussion on transition to presidential system. Whereas it is clear that every system of government has favorable or unfavorable features. As a matter of fact, today, discussions on problems that are caused by prevailing system of government continue in most of the states. States try to make balance between political stability and democratic ideals regarding the type of government they implemented. In this context, level of democratic cultural development in a state becomes the guarantee of decreasing problems within the implemented system. However, it can be stated that it is difficult to find a system that meets every needs in all dimensions.